2019
DOI: 10.17576/mh.2019.1402.14
|View full text |Cite
|
Sign up to set email alerts
|

Adult Personality and its Relationship with Stress Level and Coping Mechanism among Final Year Medical Students

Abstract: Each human being exhibits their own personality traits and each aspect of stress and coping is essential and related. The relationship between the big five personality traits, coping mechanisms and stress level among final year medical students of Universiti Kebangsaan Malaysia (UKM) was investigated in this study. In this cross-sectional study, 152 final year medical students batch 2017/2018, were randomly selected, excluding those who had chronic diseases, married and repeated final year. The questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…In terms of coping strategies, previous studies have found that extraversion (E) was positively correlated with active coping strategies, such as problem solving and seeking support (Karimzade and Besharat 2011;Vollrath and Torgersen 2000;Wang and Miao 2009;Zainah et al 2019). More specifically, Extraversion was found to be positively related to active problem-focused coping (e.g., problem solving and planning) and adaptive emotionfocused coping (e.g., positive reframing, humor, seeking support, and acceptance) (Roesch et al 2006).…”
Section: Extraversion (E)mentioning
confidence: 93%
See 2 more Smart Citations
“…In terms of coping strategies, previous studies have found that extraversion (E) was positively correlated with active coping strategies, such as problem solving and seeking support (Karimzade and Besharat 2011;Vollrath and Torgersen 2000;Wang and Miao 2009;Zainah et al 2019). More specifically, Extraversion was found to be positively related to active problem-focused coping (e.g., problem solving and planning) and adaptive emotionfocused coping (e.g., positive reframing, humor, seeking support, and acceptance) (Roesch et al 2006).…”
Section: Extraversion (E)mentioning
confidence: 93%
“…As such, their ability to cope effectively is crucial under the transactional model of stress developed by Lazarus and colleagues (Lazarus 1966;Lazarus and Folkman 1984). Broad associations observed between personality traits and coping with stress may provide important insight into individual differences in patterns of thinking, feeling, and behaving that translate to managing stress through adaptive versus maladaptive coping (Zainah et al 2019).…”
Section: Big Five Personality Traits and Coping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, research has shown that personality is associated with distinct levels of stress and coping strategies. For example, those with maladaptive personality traits, such as neuroticism, are more likely to use avoidant coping strategies (e.g., escape avoidance or self-blame), which may often lead to harmful behaviours (Afshar et al, 2015;Zainah et al, 2019). Individuals with maladaptive traits have also been shown to be more likely to experience stress and negative emotions (Vollrath and Torgersen, 2000;Zainah et al, 2019).…”
Section: Personalitymentioning
confidence: 99%
“…For example, those with maladaptive personality traits, such as neuroticism, are more likely to use avoidant coping strategies (e.g., escape avoidance or self-blame), which may often lead to harmful behaviours (Afshar et al, 2015;Zainah et al, 2019). Individuals with maladaptive traits have also been shown to be more likely to experience stress and negative emotions (Vollrath and Torgersen, 2000;Zainah et al, 2019). Such findings suggest that an individual's personality is linked to the level of emotional distress they experience, as well as the strategies they use to respond to such distress.…”
Section: Personalitymentioning
confidence: 99%